Budaya Organisasi dalam Pendidikan di UPTD SPF SMP Negeri 1 Gunung Meriah Aceh Singkil - Makmur Syukri; Miranti Adelia Afda (Journal on Education, 2024)
Organizational culture is a pattern of basic assumptions regarding the beliefs, values ​​and behavior created. This article aims to understand the organizational culture at UPTD SPF SMP Negeri 1 Gunung Meriah Aceh Singkil. The method used in this research is a descriptive qualitative research method. The research results show that the school organizational culture at UPTD SPF SMP Negeri 1 Gunung Meriah Aceh Singkil is about the discipline of the principal, teachers and administrative employees; student discipline; (2). hard work culture, namely the hard work of teachers and students; (3) competitive culture, namely competition between teachers and competition among students; c). The influence of the school organizational culture developed at UPTD SPF SMP Negeri 1 Gunung Meriah Aceh Singkil on school achievement, among others (1). the influence of school organizational culture on the achievement of UPTD SPF students at SMP Negeri 1 Gunung Meriah Aceh Singkil; (2). the achievements of UPTD SPF alumni of SMP Negeri 1 Gunung Meriah Aceh Singkil at the secondary education level, namely about parents' impressions of UPTD SPF SMP Negeri 1 Gunung Meriah Aceh Singkil, Alumnus of UPTD SPF SMP Negeri 1 Gunung Meriah Aceh Singkil at the secondary education level; d). discussion, including: (1). organizational culture developed by the school principal, (2). culture of hard work carried out by teachers, (3). student competitive culture.